Clinical epidemiology and molecular profiling of human bocavirus in faecal samples from children with diarrhoea in Guangzhou, China. (August 2015) - ZHANG, D.-M.; MA, M.-M.; WEN, W.-T.; ZHU, X.; XU, L.; HE, Z.-J.; HE, X.; WU, J.-H.; HU, Y.-W.; ZHENG, Y.; DENG, Y.; LIN, C.-J.; et al.
SUMMARY To understand the clinical epidemiology and molecular characteristics of human bocavirus (HBoV) infection in children with diarrhoea in Guangzhou, South China, we collected 1128 faecal specimens from children with diarrhoea from July 2010 to December 2012. HBoV and five other major enteric viruses were examined using real-time polymerase chain reaction. Human rotavirus (HRV) was the most prevalent pathogen, detected in 250 (22·2%) cases, followed by enteric adenovirus (EADV) in 76 (6·7%) cases, human astrovirus (HAstV) in 38 (3·4%) cases, HBoV in 17 (1·5%) cases, sapovirus (SaV) in 14 (1·2%) cases, and norovirus (NoV) in 9 (0·8%) cases. Co-infections were identified in 3·7% of the study population and 23·5% of HBoV-positive specimens. Phylogenetic analysis revealed 14 HBoV strains to be clustered into species HBoV1 with only minor variations among them. Overall, the detection of HBoV appears to partially contribute to the overall detection gap for enteric infections, single HBoV infection rarely results in severe clinical outcomes, and HBoV sequencing data appears to support conserved genomes across strains identified in this study.